Biological nutrient transformation during composting of pig manure and paper waste. Issue 6 (19th March 2017) - Wong, Jonathan W.C.; Karthikeyan, Obulisamy P.; Selvam, Ammaiyappan
ABSTRACT: Composting of pig manure is a challenging task that requires appropriate co-substrate and bulking agent to provide optimum composting conditions and reduce nitrogen loss. In this study, paper waste is co-composted with pig manure as well as wood chips as the bulking agents. These raw materials were mixed at three different ratios of paper: pig manure: wood chips = 1:1:0 (pile 1), 3:2:1 (pile 2) and 3:1:1(pile 3), respectively. Each composting pile was about 11 m 3 in size equipped with negative-pressure forced aeration. The temperature of all the three piles ranged between 43 and 76°C and therefore produced pathogen-free compost. The overall total carbon reduction of 39%, 36% and 36% were achieved from pile 1, 2 and 3, respectively. The increased with the composting period, indicating the transformation of ammoniacal-N into nitrate by nitrification activity. However, all three piles showed significant variations in soluble at different stages of composting, which could be due to the microbial assimilation and mineralization. The results revealed that the co-composting of pig manure, paper along with wood chips was optimum under the mixing ratio of 3:2:1 (pile 2).